The Effect Of Ratio To Asset And Debt To Equity Ratio On The Phenomenon Of Underpricing With The Inflation Rate As An Intervening Variable In Companies Conducting Initial Public Offerings On The Indonesian Stock Exchange - Muhammad Irza Aryasta; Rahima Br Purba; M. Irsan Nasution (Journal of Management, Economic, and Accounting, 2026)
The analysis technique used is path analysis with the help of SPSS 23 software. The results of the study indicate that (1) ROA has a significant negative effect on underpricing; (2) DER has a significant positive effect on underpricing; (3) inflation acts as an intervening variable that strengthens the effect of DER on underpricing; but does not mediate the effect of ROA on underpricing. These findings indicate that the company's fundamental factors and macroeconomic conditions simultaneously influence the initial stock price level in the Indonesian capital market.